Antibacterial activity of extracted Hemolymph from larvae and pupae of local fly species Musca Domestica and Chrysomya Megacephala - Ahmad Zorin Sahalan,; Baharudin Omar,; Aima Yusirah Mohamed,; John Jeffery, (penerbit ukm, 2006)
Natural peptides in insect vectors played an important role in the control of pathogens. Musca domestica Linnaeus and Chrysomya megacephala Fabricius were two species of local fly chosen to detect presence of antimicrobial peptide substance. The screening of the antimicrobial activity was carried using a spectrophotometric method. Results were obtained much quicker and less laborious. The results showed larva hemolymph of M. domestica lysed Bacillus subtilis and two Gram negatives, Escherichia coli and Pseudomona. aeruginosa. The pupae hemolymph only lysed E.coli. Whereas, the hemolymph of C. megacephala larva showed bactericidal effect against both of the Gram positives tested, i.e. B. subtilis and Staph. aureus. and no effect was against the Gram negatives. The pupa showed lytic activity against Staph. aureus and P. aeruginosa. As a conclusion, the larva and pupa hemolymph of M. domestica and C. megacephala demonstrated antibacterial activity. However, larva hemolymph of M. domestica and C. megacephala has broader antibacterial activity against both Gram positive and negative bacteria.